STUDENTS’ MAIN PROBLEMS IN WRITING NARRARTIVE TEXT A Descriptive Study Conducted towards Students of Manajemen Pendidikan Islam at STAI AL MUHAMMAD CEPU - Linna Endah; umi hanik ulfiah (Sekolah Tinggi Agama Islam Almuhammad Cepu, 2021)
ABSTRACTDuring conducting my English class for 3 years, only some of MPI students succeeded in writing narrative texts, and others got the standard minimum score. The problems can be mentioned as; lack of vocabularies, error and mistake in past tense structure, and also the paragraph organization. Based on the situation above, the writer wanted to figure out the main problems (mistakes and errors) faced by MPI students in writing narrative texts. By conduction this study, the writer hoped that the writer would be able find the treatment, so that students will be able improve their skill and competence in writing narrative texts. This study, the writer used descriptive qualitative research. To gain the data, the writer analyzed the students’ work in composing narrative texts (documents) and interview section. From the documents and interview section, the writer could draw the conclusion that the main mistakes and errors should be treated were: 1) the generic structure of their writing narrative texts; 2) the use of past tense structure; simple past tense, past continuous, past perfect, and past perfect continuous tense; 3) the use of incorrect elements of sentences.Key words: students’ problems, writing, narrative-text